A Pompeian house in Valparaiso: identity and bourgeois imaginary at the beginning of the 20th century - Huidobro Salazar, María Gabriela (Cuadernos de Historia, 2022)
In the mid-twentieth century, the Chilean writer Joaquín Edwards Bello offered his memories about the Pompeian house, a luxurious residence in Valparaíso, where he lived during his youth. Indeed, it is a building that remains to this day and whose characteristics evoke the houses of the Roman aristocracy in Classical Antiquity. Based on the verification of those elements inspired by the architecture and ornamentation of the ancient towns of Pompeii, this article reflects on the meaning and symbolism of that influence, in relation to the social and cultural context of Valparaíso, in the late nineteenth and early twentieth centuries.